Economic Impact Of Peste Des Petits Ruminants In Goats Of South Gujarat - Thakor, R.B.; Patel, M.D.; Kalyani, I.H.; Patel , R.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The economic impact (monetary losses) of Peste des petits ruminants (PPR) was calculated based on an epidemiological study on PPR in nearly 10% of goat population of south Gujarat (213808) during a period from June 2014 to May 2015. A total economic loss due to PPR in goats was Rs.21,33,688. The important components like losses due to mortality, weight loss, treatment cost, reproductive failure, opportunity cost and milk loss having economic significance were covered. Among such economically important variables, a loss due to mortality in PPR affected goats was 70.52%, i.e. maximum to the tune of Rs.15,04,800 of overall economic losses due to PPR. The body weight loss was the second (10.45%) most important component affecting economic loss. The other components like milk loss, reproductive loss, treatment cost and opportunity cost contributed 1.60, 4.24, 8.61 and 4.61% of overall monetary losses due to PPR in goats. Therefore, it is concluded that the higher morbidity and mortality cause heavy economic losses to the farmers. Hence, disease surveillance at regular intervals and mass vaccination programmes are urgently needed to implement for control of PPR in goats of South Gujarat.